2003
DOI: 10.1046/j.1432-1033.2003.03637.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, cloning and characterization of two thioredoxin h isoforms, HvTrxh1 and HvTrxh2, from the barley seed proteome

Abstract: Two thioredoxin h isoforms, HvTrxh1 and HvTrxh2, were identified in two and one spots, respectively, in a proteome analysis of barley (Hordeum vulgare) seeds based on 2D gel electrophoresis and MS. HvTrxh1 was observed in 2D gel patterns of endosperm, aleurone layer and embryo of mature barley seeds, and HvTrxh2 was present mainly in the embryo. During germination, HvTrxh2 decreased in abundance and HvTrxh1 decreased in the aleurone layer and endosperm but remained at high levels in the embryo. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 42 publications
(73 reference statements)
2
63
0
Order By: Relevance
“…Barley contains two thioredoxin isoforms as well as two isoforms of an NADPH-dependent thioredoxin reductase that reduce the disulfide formed in the thioredoxin active site motif CXXC after it has reduced a target protein disulfide bond (Maeda et al 2003;Shahpiri et al 2008). We have developed a proteomics-based procedure that allows identification of target disulfides in protein mixtures (Maeda et al 2005; P. Hägglund et al, manuscript in preparation).…”
Section: New Roles and Diversity Of α-Glucan-active Enzymes In Biologmentioning
confidence: 99%
“…Barley contains two thioredoxin isoforms as well as two isoforms of an NADPH-dependent thioredoxin reductase that reduce the disulfide formed in the thioredoxin active site motif CXXC after it has reduced a target protein disulfide bond (Maeda et al 2003;Shahpiri et al 2008). We have developed a proteomics-based procedure that allows identification of target disulfides in protein mixtures (Maeda et al 2005; P. Hägglund et al, manuscript in preparation).…”
Section: New Roles and Diversity Of α-Glucan-active Enzymes In Biologmentioning
confidence: 99%
“…Concerning to proposed classification based on the residue at position 101 [47] These 77 and 88 residues are implicated in the aromatic tetrahedral cluster important for thermostability of Trxs h [48], while 101 residues are involved in the R 101 KDD 104 motif critical for cell to cell movement [42].…”
Section: Vvtrx H2 Belongs To a Specific Cluster Of Trxs H Subgroup Imentioning
confidence: 99%
“…It seems that the N-terminal M 1 AEE 4 motif acts like an arm appended to the main body to VvTrx h2 and may be able to mediate protein cell to cell transport through plasmodesmata. Also the charged Glu residues (Glu3 and Glu4) play a crucial role in this cell to cell transport, since replacement of Glu residues with Ala appeared to potentiate a limited interaction between protein and plasmodesmata [47].…”
Section: Analysis Of In Silico Mutations In the Structural Motifs Invmentioning
confidence: 99%
See 1 more Smart Citation
“…In the germinating seeds the disulphide reductase thioredoxin h 33) is capable of reducing disulphide bonds in a series of target proteins, including BASI as well as different α amylase inhibitors of the CM protein family shown to act on mammalian and insect α amylases. 27) In the case of BASI, it has been demonstrated that one of its two disulphide bonds, actually situated in the three dimensional structure in the vicinity of residues interacting with AMY2 in the complex is particularly prone to reduction by thioredoxin h. The second disulphide bond in BASI is near the protease binding site and seems to be only slightly affected.…”
Section: Reactions Involving α-Amylases α-Amylase Inhibitors and Thimentioning
confidence: 99%